2010
DOI: 10.1007/s10295-010-0759-9
|View full text |Cite
|
Sign up to set email alerts
|

Didymosphaeria igniaria: a new microorganism useful for the enantioselective reduction of aryl-aliphatic ketones

Abstract: Didymosphaeria igniaria is a promising biocatalyst in asymmetric reductions of prochiral aromatic-aliphatic ketones such as acetonaphthones, acetophenones, and acetylpyridines. The organism converted the substrates mainly to (S)-alcohols. Excellent results in terms of conversion and enantioselectivity (100% yield, >99% ee) were obtained with acetonaphthones. In case of acetyl pyridines, the optical purity of the product depended on the position of the carbonyl group on the pyridine ring and followed the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The conversion of aromatic aldehydes and aromatic-aliphatic ketones such as acetophenones and acetylpyridines is not, to our knowledge, common in a single biocatalyst. Nevertheless, the filamentous fungus Didymosphaeria igniaria KCH 6670 was reported to carry out the asymmetric reductions of prochiral aromatic-aliphatic ketones, including acetonaphthones, acetophenones, and acetylpyridines, to mainly the corresponding ( S )-alcohols [ 47 ]. In the present study, the cells converted nonetheless 2.8-fold more benzaldehyde than any of the other substrates ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of aromatic aldehydes and aromatic-aliphatic ketones such as acetophenones and acetylpyridines is not, to our knowledge, common in a single biocatalyst. Nevertheless, the filamentous fungus Didymosphaeria igniaria KCH 6670 was reported to carry out the asymmetric reductions of prochiral aromatic-aliphatic ketones, including acetonaphthones, acetophenones, and acetylpyridines, to mainly the corresponding ( S )-alcohols [ 47 ]. In the present study, the cells converted nonetheless 2.8-fold more benzaldehyde than any of the other substrates ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies on enantiospecific reduction of α-tetralone ( 1 ) and β-tetralone ( 3 ), the biotransformations in Fusarium culmorum [16] and Didymosphaeria igniaria KCh 6670 [17] cultures were presented. The obtained results prompted us to test another group of available microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few manuscripts have so far reported concurrent percentage variations of two enantiomers of alcohols formed during reduction of pro-chiral ketones [16, 17]. …”
Section: Resultsmentioning
confidence: 99%
“…In another study performed with D. carota cell biocatalyst, it was reported that ( S )‐2 was obtained with 88% conversion and 95% ee 22 . In another study in the literature, it was reported that in the presence of Didymosphaeria igniaria whole‐cell biocatalyst, the asymmetric reduction of 1 to ( S )‐2 was achieved with 71% yield and 78% ee 23 . In a study conducted with whole cells of the fungus Fusarium culmorum , it was reported that ( S )‐2 was fabricated with 53% conversion and 45% ee 24 .…”
Section: Introductionmentioning
confidence: 97%